Perspective: When the cure might become the malady: the layering of multiple interventions with mandatory micronutrient fortification of foods in India. Issue 4 (28th July 2021) - Kurpad, Anura V; Ghosh, Santu; Thomas, Tinku; Bandyopadhyay, Sulagna; Goswami, Ravinder; Gupta, Arun; Gupta, Piyush; John, Anjaly T; Kapil, Umesh; Kulkarni, Bharati; Kuriyan, Rebecca; Madan, Jagmeet; et al.
ABSTRACT: When public health programs with single nutrients are perceived to have a poor impact on the target health outcome, the policy response can be to supply more, by layering additional mandatory programs upon the extant programs. However, we argue for extreme caution, because nutrients (like medicines) are beneficial in the right dose, but potentially harmful when ingested in excess. Unnecessary motivations for the reactionary layering of multiple intervention programs emerge from incorrect measurements of the risk of nutrient inadequacy in the population, or incorrect biomarker cutoffs to evaluate the extent of nutrient deficiencies. The financial and social costs of additional layered programs are not trivial when traded off with other vital programs in a resource-poor economy, and when public health ethical dilemmas of autonomy, equity, and stigma are not addressed. An example of this conundrum in India is the perception of stagnancy in the response of the prevalence of anemia to the ongoing pharmacological iron supplementation program. The reaction has been a policy proposal to further increase iron intake through mandatory iron fortification of the rice provided in supplementary feeding programs like the Integrated Child Development Services and the School Mid-Day Meal. This is in addition to the ongoing pharmacological iron supplementation as well as other voluntary iron fortifications, such as those of salt and manufactured food products. However, before supplying more, it is vital to consider why the existing program is apparently not working, along with consideration of the potential for excess intake and related harms. This is relevant globally, particularly for countries contemplating multiple interventions to address micronutrient deficiencies. Supplying more by layering multiple nutrient interventions, instead of doing it right, without thoughtful considerations of social, biological, and ethics frameworks could be counterproductive. The cure, then, might well become the malady.